2019
DOI: 10.1002/jimd.12030
|View full text |Cite
|
Sign up to set email alerts
|

The decision to discontinue screening for carnitine uptake disorder in New Zealand

Abstract: When screening for carnitine uptake disorder (CUD), the New Zealand (NZ) newborn screening (NBS) service identified infants as screen-positive if they had initial and repeat free carnitine (C0) levels of less than 5.0 μmol/L. Since 2006, the NBS service has identified two infants with biochemical and genetic features consistent with neonatal CUD and nine mothers with features consistent with maternal CUD. A review of the literature suggests that these nine women reflect less than half the true prevalence and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…A study conducted in the Faroe Islands revealed that postneonatal screening beyond 2 months of age successfully identified additional affected patients whose newborn screening results had been unremarkable [23]. The low sensitivity and specificity of newborn screening for PCD and the numerous asymptomatic mothers identified makes including PCD generally within newborn screening programmes controversial [8]. In our family, patient 2's having undergone newborn screening for PCD ultimately enabled its diagnosis in two children.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A study conducted in the Faroe Islands revealed that postneonatal screening beyond 2 months of age successfully identified additional affected patients whose newborn screening results had been unremarkable [23]. The low sensitivity and specificity of newborn screening for PCD and the numerous asymptomatic mothers identified makes including PCD generally within newborn screening programmes controversial [8]. In our family, patient 2's having undergone newborn screening for PCD ultimately enabled its diagnosis in two children.…”
Section: Discussionmentioning
confidence: 97%
“…Pilot studies are now evaluating an extension of the newborn screening panel to include PCD also in individual screening laboratories in Germany [6,7]. However, the New Zealand newborn screening programme just recently decided to discontinue screening for PCD; their reasons included poor sensitivity, a high false-positive rate, and numerous asymptomatic adults with PCD [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another new criterion that emerged with the revision of screening criteria by Andermann et al ( 2008 ) is that screening programme evaluation needs to be planned from the outset (Table 2 ). As a consequence, a programme may be modified or even discontinued based on ongoing assessment (Andermann et al 2010 ; Wilson et al 2019 ). Guidelines for evaluation include feedback from a diagnostic unit to a screening laboratory, which enables evaluation of basic aspects like prevalence, sensitivity and specificity.…”
Section: Dynamics In Screening Criteria For Rare Diseasesmentioning
confidence: 99%
“…The discussions in these publications illustrate how emerging technologies impact the dynamics of screening principles and criteria, which in turn impact the governance and operation of current screening programmes. In this paper, after introducing NBS and carrier screening, we focus on four of the criteria which have received attention in recent discussions (Grosse et al 2006 ; Bombard et al 2010 ; Wilson et al 2019 ; Sinha et al 2020 ; Modell 2020 ): treatment, test, target population and programme evaluation.…”
Section: Introductionmentioning
confidence: 99%